Disaster preparation efforts among animal handling businesses in Kumamoto Prefecture - Takaaki Fukuyama; Takatoshi Ando (Cogent Social Sciences)
In Japan, businesses that handle animals for profit manage an enormous number and species of animals, and it is highly likely that these animals will cause damage to society in the event of a disaster. This study aims to clarify the disaster prevention efforts among these businesses. Accordingly, it surveys managers of animal handling businesses in Kumamoto Prefecture, which was hit by a large-scale 7.3 earthquake in 2016. Findings indicate that the disaster prevention implementation rate after the Kumamoto earthquake was 32.8%, business continuity plan (BCP) recognition rate was 4.4%, and BCP formulation rate was 2.6%, which are all extremely low. This may be because of managers’ lack of social responsibility and the impact of regional characteristics with low awareness of disaster prevention. The results show that animal handling businesses in Kumamoto Prefecture are considerably vulnerable to large-scale earthquake disasters, and that the implementation rate and awareness of disaster prevention among managers has not sufficiently increased after the 2016 earthquake.